Effect of Corona Pandemic (Covid-19) on Mental Health And Behavior in Children (Cross Sectional Study) (Medical Forum Monthly, 2023)
Objective: To detect the effect of corona pandemic (COVID-19) on mental health and behavior in children.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Doctor Hospital Gujrat Pakistan from January 2020 to April 2021.Materials and Methods: Total 162 children from age group 01 to 12 years were selected for study who had heard about the corona pandemic (COVID-19) through media or any other source. Families who approached the hospital for check-up of a child were requested to ask few questions from their children to assess the change in mental health and behavior of children due to corona virus infection in the world. Healthy children accompanying the child who came for check-up were also included in the study. After detecting the risk factors and changes in mental health and behavior in children, immediately counseling and behavior therapy was started. The examination of risk factors associated with changes in mental health was conducted to identify potential influences.Results: Numerous factors have been identified as potential contributors to changes in children's mental health and behavior including loneliness, leaves from school, delay of examination schedule, both electronic and social media, discussion in community and newspaper. One child might be affected by more than one risk factor as well. Children may experience various unwanted changes in mental health and behavior, including sleep and appetite disturbances, anger, difficulty concentrating, fatigue, physical complaints, feelings of hopelessness, increased sensitivity and irritability, and thoughts of death.Conclusion: Many risk factors brought great unwanted changes in the mental health and behavior of the children during corona pandemic (COVID-19). Most important risk factors were social distancing and campaign on electronic and social media. Fearful, awful and frightening coverage on electronic and social media about corona pandemic may be the reason. Proper control and reduction in risk factors may be helpful in controlling such unwanted changes. Proactive and timely intervention, as well as counseling for both parents and children, can effectively mitigate adverse changes in children's mental health and behavior.